DEIXIS IN JUSTIN BIEBER’S SONG LYRICS - Sridepi Martina Manalu; Putri Andriani Purba; Andi Jaihutan Silitonga (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2022)
This thesis deal with Deixis in Justin Bieber’s Song Lyrics. It explains about how deixis works in lyric of songs such as person deixis, time deixis and place deixis. The objective of analyzing the songs were to find out the types of deixis, the most dominant type of deixis and the reason of the most dominant type of deixis in the entire songs. In this thesis, the writer was conducted by using descriptive qualitative design. The data analysis of this study was taken from album which consists of fourteen (14) titles. The result of this study showed that there were three (3) types of deixis in the album, they are person deixis, time deixis and place deixis. After analyzing the data, there are 834 data found with consist of 744 data (89,20%) indicating person deixis, 68 data (8,15%) indicating time deixis, and 22 data (2,65%) indicating place deixis. In this study the most dominant is person deixis with totally 744 data (89,20%).